2019
DOI: 10.1134/s156035471904004x
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation Diagram of One Generalized Integrable Model of Vortex Dynamics

Abstract: The article is devoted to the results of a phase topology research on a generalized mathematical model, which covers such two problems as dynamics of two point vortices enclosed in a harmonic trap in a Bose-Einstein condensate and dynamics of two point vortices bounded by a circular region in an ideal fluid. New bifurcation diagrams are obtained and three-intoone and four-into-one tori bifurcations are observed for some values of the model's physical parameters. The presence of such bifurcations in the integra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In this paper, we define a bifurcation diagram as a two-parameter family. Figure 2 shows the new type of the bifurcation diagram from this family, which was not observed in any of the works [25], [18], [28]. Such a diagram contains two "loops" with the cusped points, and one of the loops has only one vertical asymptote.…”
Section: Bifurcation Diagrammentioning
confidence: 87%
See 3 more Smart Citations
“…In this paper, we define a bifurcation diagram as a two-parameter family. Figure 2 shows the new type of the bifurcation diagram from this family, which was not observed in any of the works [25], [18], [28]. Such a diagram contains two "loops" with the cusped points, and one of the loops has only one vertical asymptote.…”
Section: Bifurcation Diagrammentioning
confidence: 87%
“…In this paper, we derive a bifurcation diagram of the momentum map in the case of a generalized system that describes the dynamics of two vortices of opposite intensities, both in an ideal fluid placed inside a circular cylinder and in a Bose-Einstein condensate enclosed in a harmonic trap. Recall that in a case of two vortices of the same sign, considered in [18], the bifurcation diagram of vortices in a Bose-Einstein condensate differs significantly from the diagram of vortices in an ideal fluid. Here we found that, on the one hand, there are diagrams similar to those constructed in the [25], [18], [28], and on the other hand, there are also diagrams that differ significantly from those had been already encountered before.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations